Quo Vadis: Konsep Meaningful Participation sebagai Implikasi Putusan MK No. 91/PUU-XVIII/202 dalam Menunjang Hak Konstitusional - Muhammad Fawwaz Farhan Farabi; Caroline Gabriela Pakpahan; Rianjani Rindu Rachmania (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
Low public participation in the political process certainly results in democracy being ineffective. The lack of socialization in the community, both in discussions regarding academic texts and in material regarding amendments to the quo law during meetings in various community groups, proves that the implementation of meaningful participation is not being implemented well. The aim and purpose of writing this article is to ensure that studies and reviews of government policies governing meaningful participation such as Law Number 13 of 2022 concerning the Second Amendment to Law Number 12 of 2011 concerning the Formation of Legislative Regulations can be carried out. The research method used in this article is normative juridical. The significance of this article is that it is hoped that it can provide an academic basis for the government to realize the appropriate and effective implementation of meaningful participation. The conclusion of this article is that it is hoped that the government can create a space for deliberative discussion and use clear nomenclature in legislation to avoid the potential for government arbitrariness in supporting the constitutional rights of its people.Keywords: Meaningful Participation; Constitutional Rights; Job Creation Law AbstrakRendahnya partisipasi masyarakat dalam proses politik tentu mengakibatkan demokrasi menjadi tidak efektif. Minimnya sosialisasi kepada masyarakat, baik dalam pembahasan terkait naskah akademik maupun dalam materi amandemen undang-undang a quo pada saat pertemuan di berbagai kelompok masyarakat, membuktikan bahwa penerapan meaningful participation tidak terlaksana dengan baik. Adapun maksud dan tujuan dari penulisan artikel ini adalah untuk memastikan kajian dan tinjauan mengenai kebijakan pemerintah yang mengatur mengenai meaningful participation seperti Undang-Undang Nomor 13 Tahun 2022 tentang Perubahan Kedua atas Undang-Undang Nomor 12 Tahun 2011 tentang Pembentukan Peraturan Perundang-Undangan dapat dilakukan. Metode penelitian yang digunakan dalam artikel ini adalah yuridis normatif. Signifikansi dalam artikel ini adalah diharapkan dapat memberikan landasan akademik bagi pemerintah untuk mewujudkan penerapan meaningful participation yang tepat dan efektif. Kesimpulan dalam artikel ini adalah diharapkan pemerintah dapat menciptakan ruang diskusi deliberatif dan penggunaan nomenklatur yang jelas dalam peraturan perundang-undangan guna menghindari potensi terjadinya kesewenang-wenangan pemerintah dalam menunjang hak konstitusional rakyatnya.Keywords: Meaningful Participation; Hak Konstitusional; Undang-Undang Cipta Kerja